Microbial Pigments as Bio-based Dyes in Textile - Qasim, Fatima; Ali, Wajid; Niaz, Kinza; Ahmad, Muhammad Sajjad; Bento, Heitor B. S. [UNESP]; Irfan, Muhammad (Springer Nature, 2025)
The textile industry is increasingly seeking sustainable alternatives to synthetic dyes due to environmental and health concerns. Microbial pigments, derived from microorganisms such as bacteria, fungi, and algae, offer a promising bio-based solution. This review provides an in-depth analysis of the potential applications of microbial pigments in textiles, focusing on their production, properties, and advantages. These pigments are highly regarded for their sustainability, as they are produced from renewable resources and have a significantly lower ecological footprint compared to conventional synthetic dyes. Additionally, they are typically biodegradable, contributing to reduced environmental impact. Microbial pigments offer a diverse range of colors, potentially surpassing the palette of synthetic dyes and introducing novel hues to the textile industry. However, their practical application faces challenges related to stability, colorfastness, and scalability. These pigments often exhibit lower color retention and are susceptible to environmental factors, necessitating advancements in production methods and dyeing techniques to enhance their durability and performance. Recent research has made significant progress in microbial fermentation technologies and genetic modifications, improving pigment stability and yield.